Towards financial inclusion: determinants of international bank account ownership - Lilianne Isabel Pavón Cuéllar (Atlantic Review of Economics (ARoEc), 2019)
This paper explores the drivers of bank account ownership, which represents a main access path to financial inclusion, considered by the United Nations as a fundamental pillar of economic growth and social inclusion in its 2030 agenda for sustainable development. The objective of the current study is to identify the supply and demand elements that affect bank account ownership internationally and use this information to build a dynamic panel that allows to validate them statistically. Given some socio-economic characteristics of potential users of financial products, bank account ownership relies not only on the access channels of these services, but also on the country's success to preserve citizen's savings incentives, such as reduction of asymmetric information within the financial sector, as well as the preservation of the international purchase power of the domestic currency. It was also determined that while more economic agents enter to the financial system, their access channels are multiplied at the same pace the information inequalities are diluted; hence these determinants of bank account ownership and financial inclusion are of endogenous nature. This research contributes to the standardization of the study of financial inclusion which is relevant yet little explored. The findings are crucial to provide guidance to government, banking, and supranational entities among others, towards more effective actions to promote the financial development, particularly in emerging countries.
Keywords: O16; G21; 330; financial inclusion; sustainable economic growth; dynamic panel; asymmetric information; precarious work